Periodicals in Medical and Health Sciences, and Health Sciences Publishing Symposiums - Bahşişoğlu, Hatice Kübra (Information World, 2014)
Scientific researches and studies, the aim and the goal of the study, how it has been prepared, its limitations, research methods, data collection techniques, sources of information and the results obtained should be announced to science world clearly and in accordance with the rules after the reliability is tested. The subject of medical and health sciences are the leading disciplines that require to share researches, new inventions, knowledge and experience rapidly and accurately. The professionals of medical and health sciences must continue to follow the information resources of their field, to search, and at least to follow the innovatios after their formal education. Various meetings have been held in our country about periodicals that have an important role in the dissemination process of knowledge and particularly about how to increase their scientific qualities. Among these, Health Sciences Publishing Symposiums for the that have been organized by ULAKBİM draw attention with their continuity and effiency. The aim of this article is to examine the subjects dealed in studies to increase the qualities of academic and scientific journals of medical and health sciences published in Turkey and especially in symposiums of periodicals for the health sciences in terms of their contributions to academic publishing. Topics mostly as journals of medical and health sciences, scientific and medical research and publication ethics, consultancy systems, editorship, responsibilities of editors, authorship and article writing, citation index, discussed in symposiums that started in 1991 and held information annually after in 2003 involve important information not only for reseachers, authors but also for editors, consultants and publishers. Besides the symposiums, it has been expected that the study of DergiPark which is the new project of ULAKBİM will contribute to our scientific periodicals. As a result, advice for the future symposiums and the points that should be completed in communique books are mentioned in the article.